Honeycomb structure, exhaust gas purification catalyst and exhaust gas purification system

By designing a ceramic columnar honeycomb structure in the exhaust gas purification system and using composite materials of conductive and non-conductive bodies for induction heating, the problem of the catalyst being unable to effectively purify the exhaust gas before reaching the activation temperature is solved, and the energy consumption and risk of structural damage of the system are reduced.

CN115209994BActive Publication Date: 2025-03-07NGK INSULATORS LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080096973.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-19
Filing Date
2020-11-16
Publication Date
2025-03-07
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

The existing exhaust gas purification system cannot effectively purify harmful gases in the exhaust gas before the catalyst reaches the activation temperature, resulting in an increase in emissions. Induction heating technology has problems such as the device size, increased power consumption and vibrating the honeycomb structure, resulting in damage to the compartment.

Method used

A ceramic columnar honeycomb structure is designed, and the composite material composed of conductive and non-conductors generates heat under the change of magnetic field to achieve induction heating, and a conductive body is arranged in the bonding material layer to heat the catalyst to reduce power consumption and risk of compartment damage.

Benefits of technology

It effectively suppresses power consumption during induction heating, reduces the damage to the compartment of the honeycomb structure, and improves the efficiency and stability of the exhaust gas purification system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115209994B_ABST
    Figure CN115209994B_ABST
Patent Text Reader

Abstract

A honeycomb structure for induction heating, which is a columnar honeycomb structure made of ceramic, has an outer peripheral wall and partition walls, the partition walls are arranged on the inner side of the outer peripheral wall and divide into a plurality of compartments, the plurality of compartments pass through from one end face to another end face to form a flow path, characterized in that a composite material composed of a conductor and a non-conductor is arranged in the compartments in an area less than 50% of the total length of the honeycomb structure from one end face, and the conductor is a conductor that generates heat due to changes in the magnetic field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a honeycomb structure, an exhaust gas purification catalyst and an exhaust gas purification system. Background Art

[0002] Automobile exhaust usually contains harmful components such as carbon monoxide, hydrocarbons, nitrogen oxides, and carbon particles due to incomplete combustion. From the perspective of reducing harm to human health, there is an increasing demand to reduce harmful gas components and particles in automobile exhaust.

[0003] However, currently, these harmful components are discharged immediately after the engine is started, that is, during a period when the catalyst temperature is low and the catalytic activity is insufficient. Therefore, the harmful components in the exhaust gas may be discharged without being purified by the catalyst before the catalyst activation temperature is reached. In order to meet such needs, it is necessary to minimize the emissions discharged without being purified by the catalyst before the catalyst activation temperature is reached, and a countermeasure using, for example, electric heating technology is known.

[0004] As such a technology, Patent Document 1 describes a method of surrounding a DOC (diesel oxidation catalyst) with an IH coil and causing the DOC itself to generate heat by induction heating, thereby purifying exhaust gas.

[0005] Patent Document 2 describes a catalyst carrier having a structure in which metal particles or metal flakes are arranged throughout a plurality of cells of a ceramic substrate, and the metal particles or metal flakes are heated by induction heating.

[0006] Patent Document 3 describes an exhaust gas purification device having a structure in which a rod-shaped conductive member is inserted into a cell of a ceramic base body and the conductive member is heated by induction heating.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 6585548

[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-188272

[0011] Patent Document 3: Japanese Patent Application Publication No. 2019-173600 Summary of the invention

[0012] The technology described in Patent Document 1 can reduce power consumption compared to external heating using an electric heater. However, the DOC described in Patent Document 1 is composed of a metal honeycomb, and effective heating of the metal honeycomb requires surrounding the entire circumference with an IH coil. Therefore, there is a problem that the size of the device used for the exhaust gas purification system increases, and the power consumption also increases. In particular, this problem is more significant in the exhaust gas purification system for large vehicles with a larger volume.

[0013] In addition, the technology described in Patent Document 2 surrounds the entire honeycomb structure with an IH coil in order to heat the metal particles or metal flakes disposed in the entire cell by induction heating. Therefore, similarly to Patent Document 1, there are problems of increased device size and increased power consumption.

[0014] Furthermore, in the technique described in Patent Document 3, since the rod-shaped conductive member is inserted into the cells of the honeycomb structure, there is a possibility that the rod-shaped conductive member may break the cells due to vibration of the honeycomb structure.

[0015] The present invention aims to provide a honeycomb structure for induction heating in view of the above situation, which can heat its own honeycomb structure by induction heating, or heat a honeycomb structure arranged on its downstream side, so that the power consumption during induction heating can be suppressed and the damage of the cells of the honeycomb structure can be well suppressed. In addition, the present invention aims to provide an exhaust gas purification catalyst and an exhaust gas purification system having the above honeycomb structure for induction heating.

[0016] The above-mentioned problems are solved by the following present invention. The present invention is defined as follows.

[0017] (1) A honeycomb structure for induction heating, which is a columnar honeycomb structure made of ceramics,

[0018] The invention has an outer peripheral wall and a partition wall, wherein the partition wall is arranged inside the outer peripheral wall and partitions a plurality of compartments, and the plurality of compartments penetrate from one end face to another end face to form a flow path.

[0019] The honeycomb structure for induction heating is characterized in that:

[0020] A composite material composed of a conductor and a non-conductor is provided in the cells in a region that is less than 50% of the total length of the honeycomb structure from one end surface,

[0021] The conductor is a conductor that generates heat due to a change in the magnetic field.

[0022] (2) A honeycomb structure for induction heating, which is a columnar honeycomb structure formed by bonding a plurality of columnar honeycomb units via a bonding material layer,

[0023] The honeycomb structure for induction heating is characterized in that:

[0024] The columnar honeycomb unit has an outer peripheral wall and a partition wall, the partition wall is arranged inside the outer peripheral wall and partitions a plurality of cells, and the plurality of cells penetrate from one end face to the other end face to form a flow path,

[0025] A conductor is provided in the bonding material layer in a region that is less than 50% of the total length of the honeycomb structure from one end surface,

[0026] The conductor is a conductor that generates heat due to a change in the magnetic field.

[0027] (3) An exhaust gas purification catalyst, characterized in that it has:

[0028] The honeycomb structure according to (1) or (2); and

[0029] a catalyst supported in the cells of the honeycomb structure,

[0030] The catalyst is at least one selected from the group consisting of an oxidation catalyst, a three-way catalyst, a NOx storage reduction catalyst, a NOx selective reduction catalyst, a hydrocarbon adsorption catalyst, a hydrocarbon oxidation catalyst, a carbon monoxide oxidation catalyst, and an ammonia slip (oxidation) catalyst.

[0031] (4) An exhaust gas purification system, characterized in that it comprises:

[0032] The honeycomb structure A according to (1) or (2), wherein the honeycomb structure A is arranged on the upstream side in the gas flow direction; and

[0033] At least one honeycomb structure B is disposed on the downstream side of the honeycomb structure.

[0034] Effects of the Invention

[0035] According to the present invention, a honeycomb structure for induction heating can be provided, which can induction heat its own honeycomb structure or heat a honeycomb structure arranged on its downstream side, so that power consumption during induction heating can be suppressed and cell damage of the honeycomb structure can be well suppressed. In addition, an exhaust gas purification catalyst and an exhaust gas purification system having the above-mentioned honeycomb structure for induction heating can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic cross-sectional view of the honeycomb structure 10 in Embodiment 1 of the present invention, which is perpendicular to the extending direction of the cells 15 .

[0037] Figure 2This is a schematic cross-sectional view of the honeycomb structure 10 in Embodiment 1 of the present invention, which is parallel to the extending direction of the cells 15 .

[0038] Figure 3 This is a schematic cross-sectional view of a honeycomb structure 20 in Embodiment 2 of the present invention, which is perpendicular to the extending direction of the cells 15 .

[0039] Figure 4 This is a schematic cross-sectional view of the honeycomb structure 20 in Embodiment 2 of the present invention, which is parallel to the extending direction of the cells 15 .

[0040] Figure 5 This is a schematic cross-sectional view of a honeycomb structure 30 for induction heating in Embodiment 3 of the present invention, which is perpendicular to the extending direction of the cells 15 .

[0041] Figure 6 This is a schematic cross-sectional view of the honeycomb structure 30 in Embodiment 3 of the present invention, which is parallel to the extending direction of the cells 15 .

[0042] Figure 7 This is a schematic cross-sectional view of a honeycomb structure 30 for induction heating in Embodiment 3 of the present invention, which is perpendicular to the extending direction of the cells 15 .

[0043] Figure 8 This is a schematic cross-sectional view of a honeycomb structure 30 for induction heating in Embodiment 3 of the present invention, which is perpendicular to the extending direction of the cells 15 .

[0044] Fig. 9 Schematic diagram of an exhaust gas purification system 50 in an embodiment of the present invention.

[0045] Fig.10 This is a graph showing the relationship between time (seconds) and temperature (° C.) in Example 1 and Comparative Example 1.

[0046] Fig.11 It is a schematic diagram of the exhaust gas purification system 51, 52, 53 in the embodiment of the present invention. DETAILED DESCRIPTION

[0047] Hereinafter, with reference to the accompanying drawings, the embodiments of the honeycomb structure for induction heating, the exhaust gas purification catalyst and the exhaust gas purification system of the present invention are described. However, the present invention is not limited to the interpretation thereof, and various changes, corrections and improvements may be made based on the knowledge of those skilled in the art without departing from the scope of the present invention.

[0048] <1. Honeycomb structure>

[0049] (Implementation Method 1)

[0050] Figure 1Detailed description is given of a schematic cross-sectional view of the honeycomb structure 10 for induction heating in the first embodiment of the present invention, which is perpendicular to the extending direction of the cells 15 . Figure 2 Detailed description is given of a schematic cross-sectional view of the honeycomb structure 10 in the first embodiment of the present invention, which is parallel to the extending direction of the cells 15 .

[0051] The honeycomb structure 10 is formed in a columnar shape and includes an outer peripheral wall 11 and ceramic partition walls 12 disposed inside the outer peripheral wall 11 to define a plurality of cells 15 extending from upstream to downstream in the gas flow direction to form flow paths.

[0052] The material of the partition wall 12 and the outer peripheral wall 11 of the honeycomb structure 10 is not particularly limited, and is usually formed of a ceramic material. For example, a sintered body with cordierite, silicon carbide, aluminum titanate, silicon nitride, mullite, alumina, silicon-silicon carbide composite material, silicon carbide-cordierite composite material as the main component can be cited, especially a sintered body with silicon-silicon carbide composite material or silicon carbide as the main component. In this specification, "silicon carbide system" means that the honeycomb structure 10 contains more than 50% by mass of silicon carbide of the entire honeycomb structure 10. The honeycomb structure 10 is mainly composed of silicon-silicon carbide composite material means that the honeycomb structure 10 contains more than 90% by mass of silicon-silicon carbide composite material (total mass) of the entire honeycomb structure 10. Here, the silicon-silicon carbide composite material contains silicon carbide particles as aggregates and silicon as a bonding material for bonding the silicon carbide particles. It is preferred that a plurality of silicon carbide particles are bonded by silicon in a manner that pores are formed between the silicon carbide particles. In addition, the honeycomb structure 10 containing silicon carbide as a main component means that the honeycomb structure 10 contains silicon carbide (total mass) accounting for 90 mass % or more of the entire honeycomb structure 10 .

[0053] Preferably, the honeycomb structure 10 is formed of at least one ceramic material selected from the group consisting of cordierite, silicon carbide, aluminum titanate, silicon nitride, mullite, and alumina.

[0054] The cell shape of the honeycomb structure 10 is not particularly limited, and is preferably a triangle, a quadrilateral, a pentagon, a hexagon, an octagon, or a combination thereof in a cross section perpendicular to the central axis of the honeycomb structure 10. Among them, quadrilaterals and hexagons are preferred from the viewpoint of easily achieving both structural strength and heating uniformity.

[0055] The outer shape of the honeycomb structure 10 is not particularly limited, and may be a column with a circular end face (cylindrical shape), a column with an elliptical end face, a column with a polygonal end face (quadrilateral, pentagon, hexagon, heptagon, octagon, etc.).

[0056] The thickness of the partition wall 12 of the honeycomb structure 10 is preferably 0.05 to 0.50 mm, and more preferably 0.10 to 0.45 mm in terms of ease of manufacturing. For example, if it is 0.10 mm or more, the strength of the honeycomb structure 10 is further improved; if it is 0.50 mm or less, the pressure loss can be reduced. It should be noted that the thickness of the partition wall 12 is an average value measured by observing the cross section in the central axis direction with a microscope.

[0057] The porosity of the partition walls 12 constituting the honeycomb structure 10 is preferably 20 to 70%. In terms of ease of production, the porosity of the partition walls 12 is preferably 20% or more, and if it is 70% or less, the strength of the honeycomb structure 10 can be maintained.

[0058] In addition, the average pore diameter of the partition wall 12 is preferably 2 to 30 μm, and more preferably 5 to 25 μm. If the average pore diameter of the partition wall 12 is 2 μm or more, it is easy to manufacture; if the average pore diameter of the partition wall 12 is 30 μm or less, the strength of the honeycomb structure 10 can be maintained. It should be noted that in this specification, the "average pore diameter" and "porosity" refer to the average pore diameter and porosity measured by mercury intrusion.

[0059] The cell density of the honeycomb structure 10 is not particularly limited, but is preferably 5 to 150 cells / cm 2 The range is more preferably 5 to 100 cells / cm 2 The range is more preferably 31 to 80 cells / cm 2 range.

[0060] The honeycomb structure 10 is manufactured as follows, that is, a blank containing a ceramic raw material is molded into a honeycomb shape to form a honeycomb molded body, and the honeycomb molded body is dried and then fired to manufacture the honeycomb structure 10, wherein the honeycomb shape has a partition wall 12, and the partition wall 12 is divided into a plurality of compartments 15, and the plurality of compartments 15 are formed from one end face to another end face to form a flow path of a fluid. In addition, when the honeycomb structure is used as the honeycomb structure 10 of the present embodiment, the outer peripheral wall and the honeycomb structure part can be extruded integrally and used directly as the outer peripheral wall, or the outer periphery of the honeycomb molded body (honeycomb structure) can be ground after molding or firing to form a specified shape, and a coating material is applied to the honeycomb structure after the outer periphery is ground to form an outer peripheral coating. It should be noted that in the honeycomb structure 10 of the present embodiment, for example, the outermost periphery of the honeycomb structure may not be ground, and a honeycomb structure having an outer periphery may be used, and the outer peripheral surface of the honeycomb structure having an outer periphery (i.e., the outer side of the outer periphery of the honeycomb structure) is further coated with the above-mentioned coating material to form an outer peripheral coating. That is, in the former case, on the outer peripheral surface of the honeycomb structure, only the outer peripheral coating formed by the coating material becomes the outer peripheral wall located at the outermost periphery. On the other hand, in the latter case, the outer peripheral surface of the honeycomb structure is formed with an outer peripheral wall of a two-layer structure located at the outermost periphery, which is further laminated with the outer peripheral coating formed by the coating material. The outer peripheral wall can also be extruded integrally with the honeycomb structure portion and directly fired, and used as the outer peripheral wall in a state where no outer peripheral processing is performed.

[0061] It should be noted that the honeycomb structure 10 is not limited to an integral honeycomb structure 10 having a partition wall 12 integrally formed therein, and may be, for example, a honeycomb structure 10 having a structure in which a plurality of columnar honeycomb units are combined by means of a bonding material layer (hereinafter sometimes referred to as a "bonded honeycomb structure"), wherein the columnar honeycomb unit has a ceramic partition wall 12, and a plurality of compartments 15 are formed by partitioning the partition walls 12, and the plurality of compartments 15 form a flow path for a fluid.

[0062] A composite material 13 composed of a conductor and a non-conductor is provided in a cell 15 in a region of less than 50% of the total length from one end face of the honeycomb structure 10. The composite material 13 is filled in the cell 15. The conductor contained in the composite material 13 is a conductor that generates heat due to a change in a magnetic field. The honeycomb structure 10 includes a conductor that generates heat due to a change in a magnetic field in the cell 15 in a region of less than 50% of the total length from one end face, and only the region of less than 50% of the total length from one end face of the honeycomb structure 10 is surrounded by a coil and induction heated, thereby generating heat for the conductor. When one end face of the total length is the end face on the upstream side in the gas flow direction, the conductor provided in the region of less than 50% of the total length from the upstream side of the honeycomb structure 10 generates heat, so that the gas heated on the upstream side in the cell 15 of the honeycomb structure 10 moves to the downstream side, thereby also heating the downstream side of the honeycomb structure 10. On the other hand, when one end face of the entire length is the end face on the downstream side in the gas flow direction, the gas heated by the honeycomb structure 10 tends to the downstream side by heating the conductor arranged in the area less than 50% of the entire length of the honeycomb structure 10 from the downstream side, thereby further improving the effect of heating other carriers arranged on the downstream side of the honeycomb structure 10. Therefore, in the honeycomb structure 10, it is not necessary to surround the entire length with a coil for heating, and the honeycomb structure 10 can be heated as a whole, or other honeycomb structures arranged downstream thereof can be heated at the same time. Therefore, the power consumption during induction heating can be suppressed. In addition, the structure of the exhaust gas purification system using the honeycomb structure 10 can be simplified. In addition, the composite material 13 not only includes a conductor, but also includes a non-conductor whose thermal expansion coefficient or Young's modulus is smaller than that of the conductor. Therefore, the thermal stress generated by the thermal expansion of the composite material 13 when the honeycomb structure 10 is heated is alleviated, and the damage of the compartment 15 can be well suppressed.

[0063] In addition, as described later, the conductor carried is usually a metal with a higher density than the material of the honeycomb structure 10, and therefore has the following characteristics, that is, due to its heat capacity, once heated, the heated part is not easy to cool down compared with the case without the conductor. This effect is an advantage for further improving the effect of heating. In particular, by making the thickness of the partition wall 12 thinner and using a lightweight honeycomb structure 10, the heating effect can be improved. In addition, for example, by configuring the conductor only in the area on the downstream side, it can be made difficult to reduce the temperature of the exhaust gas tending to the downstream. Furthermore, in order to reduce the mechanical strength caused by making the honeycomb structure 10 lightweight, a conductor can also be configured on the downstream side to increase the density of the honeycomb structure 10 as a whole, thereby compensating for the mechanical strength.

[0064] The size of the honeycomb structure 10 is not particularly limited, but preferably has a diameter of 150 mm or more or a volume of 3 L or more. If formed into such a size, the honeycomb structure 10 can be used in large vehicles such as diesel vehicles, liquefied natural gas vehicles, compressed natural gas vehicles, or synthetic fuel vehicles, and the effect of reducing power consumption during induction heating is further increased.

[0065] The composite material 13 may be provided in the cells 15 in an area of ​​40% or less, 30% or less, or 20% or less of the total length of the honeycomb structure 10 .

[0066] It is preferable that no plugging portion is provided on the downstream end surface of the honeycomb structure 10. With such a configuration, the pressure loss does not increase, and the gas can be sent to the downstream side more uniformly, which is also effective in suppressing power consumption.

[0067] The compartments 15 filled with the composite material 13 can be arranged in every other compartment, every other compartment, or continuously for the compartments adjacent in the vertical and horizontal directions. There is no restriction on the number or arrangement of the compartments 15 filled with the composite material 13, and they can be appropriately designed as needed. From the viewpoint of improving the heating effect, it is preferred to increase the number of compartments filled with the composite material 13, but from the viewpoint of reducing the pressure loss, it is preferred to minimize the number of compartments filled with the composite material 13.

[0068] The composite material 13 preferably contains 50 to 95% by mass of the conductor. If the content of the conductor in the composite material 13 is 50% by mass or more, the induction heating efficiency of the honeycomb structure 10 is better. If the content of the conductor in the composite material 13 is 95% by mass or less, the thermal expansion of the composite material 13 when the honeycomb structure 10 is heated is further alleviated, so that the cell 15 can be better suppressed from being damaged. The composite material 13 more preferably contains 55 to 90% by mass of the conductor, and further preferably contains 60 to 85% by mass of the conductor.

[0069] The porosity of the composite material 13 is preferably 30 to 70%. If the porosity of the composite material 13 is 30% or more, the cells 15 filled with the composite material 13 can be better used as exhaust gas flow paths. If the porosity of the composite material 13 is 70% or less, the induction heating performance of the honeycomb structure 10 is better. The porosity of the composite material 13 is more preferably 35 to 65%, and further preferably 40 to 60%. It should be noted that the porosity of the composite material 13 supported on the honeycomb structure 10 is difficult to measure by mercury intrusion from the perspective of cutting out a sample. Therefore, in this case, it can be measured by image analysis.

[0070] The conductor included in the composite material 13 is preferably a porous body. With such a configuration, the durability of the composite material 13 is improved. Examples of the material of the porous conductor include Fe-18 mass % Cr-9 mass % Ni, Cu, and the like.

[0071] The conductor contained in the composite material 13 is preferably a magnetic body. According to such a structure, the induction heating characteristics of the honeycomb structure 10 are further improved. The magnetic body constituting the conductor is a magnetic material, which is magnetized by the magnetic field, and the state of magnetization also changes according to the strength of the magnetic field. The curve representing this change is the "magnetization curve". The magnetization curve is sometimes scaled by the magnetic field H on the horizontal axis and the magnetic flux density B on the vertical axis (B-H curve). The state in which no magnetic field is applied to the magnetic material at all is called the demagnetized state, which is represented by the origin O. If a magnetic field is applied, a curve in which the magnetic flux density increases and saturates starting from the origin O is drawn. This curve is the "initial magnetization curve". The slope of the straight line connecting the points on the initial magnetization curve and the origin is the "magnetic permeability". The magnetic permeability measures the ease of magnetization of the magnetic material in the sense of magnetic field penetration. The magnetic permeability at the point where the magnetic field is smaller near the origin is the "initial magnetic permeability", and the maximum magnetic permeability on the initial magnetization curve is the "maximum magnetic permeability".

[0072] The magnetic body constituting the conductor preferably has a maximum magnetic permeability of 500 or more. According to such a configuration, when the honeycomb structure 10 is dielectrically heated, the temperature can be raised to the temperature at which the moisture is vaporized (about 100°C) in a short time, and then raised to the temperature at which the catalyst is activated (about 300°C). The magnetic body constituting the conductor more preferably has a maximum magnetic permeability of 1000 or more, and further preferably has a maximum magnetic permeability of 2000 or more. Examples of magnetic bodies having a maximum magnetic permeability of 500 or more include: a balance of Fe-10 mass% Si-5 mass% Al, 49 mass% Co-49 mass% Fe-2 mass% V, a balance of Fe-36 mass% Ni, a balance of Fe-45 mass% Ni, a balance of Fe-35 mass% Cr, a balance of Fe-18 mass% Cr, a balance of Fe-16 mass% Cr-8 mass% Al, and the like.

[0073] The magnetic material constituting the conductor preferably has a Curie point of 450°C or higher. If the Curie point of the magnetic material constituting the conductor is 450°C or higher, it is possible to reach a honeycomb temperature sufficient for raising the catalyst temperature to above the catalyst activation temperature. Examples of magnetic materials having a Curie point of 450°C or higher include: a balance of Co-20% by mass Fe, a balance of Co-25% by mass Ni-4% by mass Fe, a balance of Fe-15 to 35% by mass Co, a balance of Fe-17% by mass Co-2% by mass Cr-1% by mass Mo, a balance of Fe-49% by mass Co-2% by mass V, a balance of Fe-18% by mass Co-10% by mass Cr-2% by mass Mo-1% by mass Al, a balance of Fe-27% by mass Co-1% by mass N b, balance Fe-20 mass% Co-1 mass% Cr-2 mass% V, balance Fe-35 mass% Co-1 mass% Cr, pure cobalt, pure iron, electromagnetic soft iron, balance Fe-0.1-0.5 mass% Mn, balance Fe-3 mass% Si, balance Fe-6.5 mass% Si, balance Fe-18 mass% Cr, balance Fe-16 mass% Cr-8 mass% Al, balance Ni-13 mass% Fe-5.3 mass% Mo, balance Fe-45 mass% Ni, etc. Here, the Curie point of a magnetic body refers to the temperature at which the ferromagnetic property is lost.

[0074] The magnetic body constituting the conductor preferably has a resistivity of 20 μΩcm or more at 25°C. According to such a configuration, the calorific value of induction heating can be further increased. As a magnetic body having a resistivity of 50 μΩcm or more at 25°C, for example, there are: a balance of Fe-18 mass % Cr, a balance of Fe-13 mass % Cr-2 mass % Si, a balance of Fe-20 mass % Cr-2 mass % Si-2 mass % Mo, a balance of Fe-10 mass % Si-5 mass % Al, a balance of Fe-18 mass % Co-10 mass % Cr-2 mass % Mo-1 mass % Al, a balance of Fe-36 mass % Ni, a balance of Fe-45 mass % Ni, a balance of Fe-49 mass % Co-2 mass % V, a balance of Fe-18 mass % Co-10 mass % Cr-2 mass % Mo-1 mass % Al, a balance of Fe-17 mass % Co-2 mass % Cr-1 mass % Mo, etc.

[0075] The magnetic body constituting the conductor preferably has a coercive force of 40 A / m or more. According to such a structure, when the honeycomb structure 10 is dielectrically heated, the temperature can be raised to the temperature at which the water vaporizes (about 100° C.) in a short time, and then to the temperature at which the catalyst is activated (about 300° C.). As magnetic bodies having a coercive force of 40 A / m or more, there are: a balance of Fe-35 mass % Co, a balance of Fe-20 mass % Co-1 mass % V, a balance of Fe-13 mass % Cr-2 mass % Si, a balance of Fe-18 mass % Cr, a balance of Fe-16 mass % Cr-8 mass % Al, a balance of Fe-49 mass % Co-2 mass % V, a balance of Fe-18 mass % Co-10 mass % Cr-2 mass % Mo-1 mass % Al, a balance of Fe-17 mass % Co-2 mass % Cr-1 mass % Mo, etc.

[0076] The material of the non-conductor included in the composite material 13 is not particularly limited, and may be glass, crystallized glass, ceramic containing silicate, boric acid or borosilicate, or glass, crystallized glass, ceramic containing other oxides.

[0077] Next, the manufacturing method of the honeycomb structure 10 is described. First, a honeycomb structure having ceramic partition walls and a plurality of compartments formed by the partition walls is produced. For example, in the case of producing a honeycomb structure containing cordierite, first, a cordierite raw material is prepared as a blank material. For the cordierite raw material, since each component is combined according to the theoretical composition of cordierite crystals, a silica source component, a magnesium oxide source component, and an aluminum oxide source component are combined. Among them, as the silica source component, quartz and fused silica are preferably used, and further, the particle size of the silica source component is preferably 100 to 150 μm.

[0078] As the magnesium oxide source component, for example, talc, magnesite, etc. can be mentioned. Among them, talc is preferred. The content of talc in the cordierite raw material is preferably 37 to 43% by mass. The particle size (average particle size) of talc is preferably 5 to 50 μm, more preferably 10 to 40 μm. In addition, the magnesium oxide (MgO) source component may contain Fe2O3, CaO, Na2O, K2O, etc. as impurities.

[0079] As the alumina source component, it is preferred to contain at least one of alumina and aluminum hydroxide in terms of less impurities. In addition, the content of aluminum hydroxide in the cordierite forming raw material is preferably 10 to 30% by mass, and the content of alumina is preferably 0 to 20% by mass.

[0080] Next, a material for a blank (additive) to be added to the cordierite forming raw material is prepared. As the additive, at least a binder and a pore former are used. In addition to the binder and the pore former, a dispersant or a surfactant may be used.

[0081] As a pore-forming agent, a substance that can react with oxygen below the firing temperature of cordierite and be oxidatively removed, or a low-melting-point reaction substance having a melting point at a temperature below the firing temperature of cordierite can be used. As a substance that can be oxidatively removed, for example, resin (especially granular resin), graphite (especially granular graphite), etc. can be cited. As a low-melting-point reaction substance, at least one metal selected from the group consisting of iron, copper, zinc, lead, aluminum and nickel, an alloy with these metals as the main component (for example, carbon steel, cast iron, stainless steel in the case of iron), or an alloy with two or more as the main components can be used. Among them, the low-melting-point reaction substance is preferably a powdery or fibrous iron alloy. Furthermore, its particle size or fiber diameter (average diameter) is preferably 10 to 200 μm. The shape of the low-melting-point reaction substance can be cited as: spherical, diamond-shaped, candy-shaped, etc. If it is these shapes, it is easy to control the shape of the pores, so it is preferred.

[0082] Examples of binders include hydroxypropylmethylcellulose, methylcellulose, hydroxyethylcellulose, carboxymethylcellulose, and polyvinyl alcohol. Examples of dispersants include dextrin and polyols. Examples of surfactants include fatty acid soaps. It should be noted that the additives may be used alone or in combination of two or more.

[0083] Next, 3 to 8 parts by mass of a binder, 3 to 40 parts by mass of a pore former, 0.1 to 2 parts by mass of a dispersant, and 10 to 40 parts by mass of water are mixed with respect to 100 parts by mass of a cordierite forming raw material, and these materials for a blank are kneaded to prepare a blank.

[0084] Next, the prepared blank is formed into a honeycomb shape by extrusion molding, injection molding, compression molding, etc. to obtain a raw honeycomb molded body. From the perspective of easy continuous molding, for example, the ability to orient cordierite crystals, the extrusion molding method is preferably used. The extrusion molding method can be performed using a vacuum clay kneader, a piston extruder, a twin-screw continuous extruder, and the like.

[0085] Next, the honeycomb formed body is dried and adjusted to a predetermined size to obtain a honeycomb dried body. The honeycomb formed body can be dried by hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, freeze drying, etc. It should be noted that, from the perspective of being able to dry the entire body quickly and uniformly, it is preferred to dry by combining hot air drying with microwave drying or dielectric drying.

[0086] Next, a material in which a conductive material composed of a desired magnetic material and a non-conductive material composed of glass are mixed is filled in the cells in the region of 50% or less of the entire length of the honeycomb dried body from the upstream side. Specifically, for example, magnetic powder and glass powder are mixed in a volume ratio of 9:1, and a binder, a dispersant, and water are mixed therein to prepare a slurry for forming a composite material.

[0087] Next, a mask is applied to a portion of the cells of the end face on the upstream side of the honeycomb dry body, and the end face is immersed in a storage container storing a slurry for forming a composite material, and the slurry for forming a composite material is filled into the cells to which the mask is not applied. At this time, the slurry for forming a composite material is filled in the cells of the honeycomb dry body in an area less than 50% of the total length from one end face. Then, it is dried and fired, thereby obtaining a honeycomb structure in which the composite material is filled in the cells in an area less than 50% of the total length from one end face. The above-mentioned drying conditions can be the same as the conditions for drying the honeycomb formed body. In addition, as for the above-mentioned firing conditions, when a cordierite raw material is used, it is usually fired at a temperature of 1410 to 1440°C in an atmospheric atmosphere for 3 to 15 hours.

[0088] As a method for filling the slurry for forming a composite material, a simple method is to press the paste-like material with a scraper such as a squeegee. The depth can be easily controlled by the number of times the squeegee is pressed.

[0089] In addition, when the honeycomb structure is made in a state where the outer peripheral wall is formed on its outer peripheral surface, the outer peripheral surface can be ground to make it a state where the outer peripheral wall is removed. In the subsequent process, a coating material is applied to the periphery of the honeycomb structure from which the outer peripheral wall has been removed to form an outer peripheral coating. In addition, when the outer peripheral surface is ground, a part of the outer peripheral wall can be ground and removed, and the coating material can be used to form an outer peripheral coating on the part. When preparing the coating material, for example, a biaxial rotating vertical mixer can be used for preparation.

[0090] In addition, the coating material may further contain colloidal silica, an organic binder, clay, etc. It should be noted that the amount of the organic binder used is preferably 0.05 to 0.5% by mass, more preferably 0.1 to 0.2% by mass. In addition, the amount of clay used is preferably 0.2 to 2.0% by mass, more preferably 0.4 to 0.8% by mass.

[0091] The outer peripheral surface of the honeycomb structure previously produced is coated with a coating material, and the coated coating material is dried to form an outer peripheral coating layer. By configuring in this way, cracking of the outer peripheral coating layer during drying and heat treatment can be effectively suppressed.

[0092] As a coating method of the coating material, for example, the following method can be cited, that is, the honeycomb structure is placed on a rotating table, rotated, and the coating material is ejected from a blade-shaped coating nozzle, and the coating nozzle is pressed along the periphery of the honeycomb structure to apply the coating. By constituting like this, the coating material can be applied with a uniform thickness. In addition, the surface roughness of the peripheral coating formed becomes smaller, and a peripheral coating with excellent appearance and not easily damaged by thermal shock can be formed.

[0093] It should be noted that when the outer peripheral surface of the honeycomb structure is ground to remove the outer peripheral wall, the coating material is applied to the entire outer peripheral surface of the honeycomb structure to form the outer peripheral coating. On the other hand, when the outer peripheral wall exists on the outer peripheral surface of the honeycomb structure, or a part of the outer peripheral wall is removed, the coating material can be partially applied to form the outer peripheral coating, and of course, the coating material can also be applied to the entire area of ​​the outer peripheral surface of the honeycomb structure to form the outer peripheral coating.

[0094] There is no particular limitation on the method for drying the applied coating material (i.e., the undried peripheral coating). For example, from the viewpoint of preventing drying cracks, the following method can be preferably adopted, namely, after drying the coating material at room temperature for more than 24 hours to remove more than 25% of the moisture in the coating material, the coating material is kept at 600°C in an electric furnace for more than 1 hour to remove moisture and organic matter.

[0095] (Implementation Method 2)

[0096] Figure 3 Detailed description is given of a schematic cross-sectional view of a honeycomb structure 20 for induction heating in a second embodiment of the present invention, which is perpendicular to the extending direction of the cells 15 . Figure 4 Detailed cross-sectional view of the honeycomb structure 20 in Embodiment 2 of the present invention, which is parallel to the extending direction of the cells 15, is described in FIG.

[0097] The configuration of the honeycomb structure 20 for induction heating in the second embodiment of the present invention is different from the honeycomb structure 10 for induction heating in the first embodiment of the present invention only in the configuration of the composite material 14. That is, in the honeycomb structure 20, the composite material 14 composed of a conductor and a non-conductor is provided in the cell 15 in the region of 50% or less of the total length from one end face, and the composite material 14 is provided in the form of a thin film on the wall surface of the cell 15. The cell 15 provided with the composite material 14 may be provided in every other cell, every multiple cells, or continuously for the cells adjacent in the vertical and horizontal directions.

[0098] The honeycomb structure 20 includes a conductor that generates heat due to a change in the magnetic field in the cell 15 in an area that is less than 50% of the total length from one end face, and only the area that is less than 50% of the total length from one end face of the honeycomb structure 20 is surrounded by a coil and induction heated, thereby causing the conductor to generate heat. Therefore, as described in Embodiment 1 of the present invention, the power consumption of the honeycomb structure 20 during induction heating can be suppressed. In addition, the structure of the exhaust gas purification system using the honeycomb structure 20 can be simplified. In addition, the composite material 14 includes not only the conductor, but also a non-conductor whose thermal expansion coefficient or Young's modulus is smaller than that of the conductor. Therefore, when the honeycomb structure 20 is heated, the thermal stress generated by the thermal expansion of the composite material 14 is alleviated, and the damage of the cell 15 can be well suppressed.

[0099] In the honeycomb structure 20 , the composite material 14 is provided in a thin film shape on the partition wall surface of the cell 15 , so that the cell 15 provided with the composite material 14 can be better used as an exhaust gas flow path.

[0100] The thickness of the film-like composite material 14 is preferably 5 to 100 μm. If the thickness of the composite material 14 is 5 μm or more, the induction heating efficiency of the honeycomb structure 10 is better. In addition, if the thickness of the composite material 14 is 100 μm or less, the cell 15 provided with the composite material 14 is better used as an exhaust gas flow path. The thickness of the film-like composite material 14 is more preferably 5 to 60 μm, and further preferably 10 to 40 μm.

[0101] The method for manufacturing the honeycomb structure 20 in the second embodiment of the present invention differs from the method for manufacturing the honeycomb structure 10 in the first embodiment of the present invention only in the composite material forming step. Therefore, an example of the composite material forming step in the method for manufacturing the honeycomb structure 20 will be described below.

[0102] In the process of forming a composite material in the method for manufacturing the honeycomb structure 20, first, a binder, a dispersant, and water are mixed in a material in which a conductor and a non-conductor are mixed to prepare a paste, and the paste is injected into the cell. Next, after drying and degreasing, the paste is sintered on the surface of the partition wall in the cell under a vacuum atmosphere, and is arranged to cover the surface of the partition wall in the cell of the honeycomb dried body. In this way, the composite material 14 arranged in a thin film on the surface of the partition wall 12 of the cell 15 can be produced.

[0103] (Implementation 3)

[0104] Figure 5 Detailed description is given of a schematic cross-sectional view of a honeycomb structure 30 for induction heating in accordance with a third embodiment of the present invention, which is perpendicular to the extending direction of the cells 15 . Figure 6Detailed cross-sectional view of a honeycomb structure 30 in Embodiment 3 of the present invention, which is parallel to the extending direction of the cells 15, is described in FIG.

[0105] The honeycomb structure 30 is formed in a columnar shape. The honeycomb structure 30 is formed by bonding a plurality of columnar honeycomb units 17 via a bonding material layer 18. The honeycomb unit 17 includes an outer peripheral wall 11 and a ceramic partition wall 12, which is disposed inside the outer peripheral wall 11 and partitions a plurality of cells 15, which extend from upstream to downstream in the gas flow direction to form a flow path.

[0106] The bonding material constituting the bonding material layer 18 is not particularly limited as long as it can bond the surfaces of the outer peripheral wall 11 of the honeycomb unit 17 to each other with good bonding force. The bonding material constituting the bonding material layer 18 includes, for example, inorganic particles, and as other components, inorganic fibers and colloidal oxides may be included. In addition, when the honeycomb unit 17 is bonded, a bonding material prepared as follows can be used, that is, in addition to these components, an organic adhesive such as methyl cellulose, carboxymethyl cellulose, a dispersant, water, etc. are added as needed, and they are mixed and kneaded using a mixer such as a mixer to form a paste to obtain a bonding material. As for the thickness of the bonding material layer, from the viewpoint of the bonding property between the honeycomb units 17, it is preferably 0.3 to 2 mm, and more preferably 0.5 to 1.5 mm.

[0107] As the constituent material of the inorganic particles contained in the bonding material constituting the bonding material layer 18, for example, it is preferred to use: ceramics selected from the group consisting of silicon carbide, silicon nitride, cordierite, alumina, mullite, zirconium oxide, zirconium phosphate, aluminum titanate, titanium dioxide and combinations thereof, Fe-Cr-Al metals, nickel metals, silicon-silicon carbide composite materials, etc.

[0108] As inorganic fibers contained in the bonding material constituting the bonding material layer 18, ceramic fibers such as aluminum silicate, mullite, and silicon carbide, and metal fibers such as copper and iron can be preferably used. As colloidal oxides, silica sol, alumina sol, etc. can be preferably cited. Colloidal oxides are preferably used to impart appropriate adhesive force to the bonding material. In addition, by drying and degreasing, they can be combined with inorganic fibers and inorganic particles, so that the dried bonding material becomes a component with excellent heat resistance and the like and is strong.

[0109] The honeycomb structure 30 is provided with a conductor 16 in the bonding material layer 18 in a region that is less than 50% of the total length from one end face. The conductor 16 is a conductor that generates heat due to changes in the magnetic field, and can be formed of the same material as the conductor included in the composite materials 13 and 14 given in embodiments 1 and 2 of the present invention.

[0110] The honeycomb structure 30 includes a conductor 16 that generates heat due to changes in the magnetic field in the bonding material layer 18 in an area that is less than 50% of the total length from one end face, and only the area that is less than 50% of the total length from one end face of the honeycomb structure 30 is surrounded by a coil and induction heated, thereby causing the conductor 16 to generate heat. Therefore, as described in embodiments 1 and 2 of the present invention, the power consumption of the honeycomb structure 30 during induction heating can be suppressed. In addition, the structure of the exhaust gas purification system using the honeycomb structure 30 can be simplified. In addition, since the conductor 16 is arranged in the bonding material layer 18, the thermal expansion of the honeycomb unit 17 when the honeycomb structure 30 is heated is alleviated, and the damage of the compartment 15 can be well suppressed. In addition, the conductor 16 is arranged in the bonding material layer 18, rather than in the compartment 15 that becomes the exhaust gas flow path, so the exhaust gas purification efficiency is better.

[0111] The conductor 16 may be provided in the bonding material layer 18 so as to be mixed with the bonding material constituting the bonding material layer 18. Alternatively, the conductor 16 may be provided in the bonding material layer 18 so as to be disposed in a part thereof.

[0112] Figure 5 In the example shown, the conductor 16 is arranged in the bonding material layer 18 in a ring shape so as to surround the plurality of honeycomb units 17. In addition, in the bonding material layer 18, the layer in which the conductor 16 and the bonding material are mixed can be arranged in a ring shape so as to surround the plurality of honeycomb units 17. According to such a configuration, since the conductor 16 is arranged in a ring shape, the current is easily flowed in a manner surrounding the conductor 16 arranged in a ring shape due to electromagnetic induction heating, so that eddy currents are easily generated. Therefore, even at a relatively low frequency of less than tens of kHz, electromagnetic induction heating can be fully performed. In addition, since eddy currents are easily generated by the conductor 16 arranged in a ring shape, the conductor 16 is not restricted by the Curie point of materials such as ferromagnetic bodies, and a honeycomb structure 30 with a good heating rate can be obtained.

[0113] In the cross section of the honeycomb structure 30 perpendicular to the extending direction of the cells 15, the arrangement of the conductors 16 in the bonding material layer 18 is not particularly limited, and may be, for example, Figure 7 and Figure 8 Configure as shown. Figure 7 In the embodiment, the conductors 16 are arranged in independent rings so as to surround the honeycomb units 17 adjacent to each other in the vertical and horizontal directions. Figure 8 In the embodiment, the conductors 16 are arranged in independent ring shapes so as to surround all the honeycomb units 17 provided on the outermost sides.

[0114] The manufacturing method of the honeycomb structure 30 in the third embodiment of the present invention is similar to the manufacturing method of the honeycomb structure 10 in the first embodiment of the present invention, and is manufactured until a honeycomb dried body is formed. Then, a bonding material is applied between the respective surfaces to be bonded of the plurality of honeycomb dried bodies, and the bonding is performed with the bonding material layer interposed therebetween. In this bonding process, a plurality of honeycomb units are stacked along an L-shaped receiving plate with the bonding material layer interposed therebetween, and after forming a desired stacked structure, the entirety is pressurized, thereby enabling bonding.

[0115] When the bonding material is applied between the surfaces to be bonded of the plurality of honeycomb dried bodies, a conductor made of a desired material is mixed with the bonding material, or the bonding material and the conductor are applied separately so that the conductor forms a part of the bonding material layer.

[0116] <2. Exhaust Gas Purification Catalytic Converter>

[0117] The exhaust gas purification catalyst 40 in the embodiment of the present invention comprises: any one of the honeycomb structures 10, 20, and 30 in the embodiments 1 to 3 of the present invention; and a catalyst, which is carried in the cells 15 of the honeycomb structures 10, 20, and 30. The catalyst carried in the cells 15 of the honeycomb structures 10, 20, and 30 is selected from oxidation catalysts, three-way catalysts, NO x Storage reduction catalyst, NO x At least one of the group consisting of a reduction catalyst, a hydrocarbon adsorption catalyst, a hydrocarbon oxidation catalyst, a carbon monoxide oxidation catalyst, and an ammonia slip (oxidation) catalyst is selected.

[0118] The catalyst can be appropriately selected according to the desired exhaust gas purification purpose. Hereinafter, a specific use example of the exhaust gas purification catalyst 40 in the embodiment of the present invention is described. In addition, the catalyst loading method is not particularly limited, and can be carried out according to the conventional loading method of loading the catalyst on the honeycomb structure.

[0119] <3. Exhaust gas purification system>

[0120] Fig. 9 Schematic diagram of an exhaust gas purification system 50 in an embodiment of the present invention is shown in FIG. The exhaust gas purification system 50 comprises: a honeycomb structure 10, which is arranged on the upstream side in the gas flow direction; and a honeycomb structure 60 and a honeycomb structure 70, which are arranged on the downstream side of the honeycomb structure 10. The number of honeycomb structures arranged on the downstream side of the honeycomb structure 10 is not limited to two, and may be one, or may be three or more. The position where the conductor 16 of the honeycomb structure 10 is provided may be an area less than 50% of the total length from the end face on the upstream side in the gas flow direction, or may be an area less than 50% of the total length from the end face on the downstream side in the gas flow direction.

[0121] Each honeycomb structure of the exhaust gas purification system 50 can carry a suitable catalyst according to the desired purpose. For example, the honeycomb structure 10 can be an exhaust gas purification catalyst 40 carrying a diesel oxidation catalyst, and either the honeycomb structure 60 or the honeycomb structure 70 can be a diesel particulate filter.

[0122] In addition, the honeycomb structure 60 and the honeycomb structure 70 may be selected from a honeycomb structure carrying a selective reduction catalyst, a honeycomb structure carrying NO x At least one of the group consisting of a honeycomb structure for storing catalysts, a honeycomb structure for carrying an ammonia slip catalyst, a honeycomb structure for carrying a three-way catalyst, and a honeycomb structure for carrying a hydrocarbon adsorption catalyst.

[0123] The exhaust gas purification system 50 has a coil wiring 47 spirally wrapped around the outer periphery of the exhaust gas purification catalyst 40. The coil wiring 47 can be provided only in the outer peripheral portion of the honeycomb structure 10 corresponding to the composite material 13 provided in the compartment 15 in the region of 50% or less of the total length from one end face, the heating efficiency of the honeycomb structure 10 is good, and the exhaust gas purification system 50 can be simplified.

[0124] The exhaust gas purification system 50 has a metal tube 44, which stores the honeycomb structure 10, 60, 70 and the coil wiring 47 via an inorganic mat material 46. The exhaust gas purification system 50 can be arranged at the expanded diameter portion of the metal tube 44. In addition, the exhaust gas purification system 50 can be used as a urea selective catalyst reduction system by providing a nozzle 43 for spraying urea water between the honeycomb structure 10 and the honeycomb structures 60 and 70. At this time, it is preferred to provide a mixer 45 on the downstream side of the nozzle 43 for spraying urea water to mix the exhaust gas and the urea water.

[0125] Fig. 9 An example of using the honeycomb structure 10 in embodiment 1 of the present invention for the exhaust gas purification system 50 is shown, but it is not limited to this. The honeycomb structure 20 or the honeycomb structure 30 in embodiments 2 and 3 of the present invention can be used in the exhaust gas purification system 50 instead of the honeycomb structure 10.

[0126] In the exhaust gas purification system 50, the temperature of the honeycomb structure 10 is increased due to the change in the magnetic field corresponding to the alternating current flowing through the coil wiring 47. At this time, the conductor of the composite material 13 arranged in the compartment 15 in the area of ​​the honeycomb structure 10 that is less than 50% of the total length from one end face generates heat, thereby heating the entire length of the honeycomb structure 10. Accordingly, when the honeycomb structure 10 carries a catalyst, the increase in the temperature of the honeycomb structure 10 increases the temperature of the catalyst carried by the catalyst carrier contained in the honeycomb structure 10, and the catalytic reaction is promoted. In simple terms, carbon monoxide (CO), nitrogen oxides (NO x ), hydrocarbons (CH) are oxidized or reduced to carbon dioxide (CO2), nitrogen (N2), and water (H2O).

[0127] Furthermore, the gas heated by passing through the honeycomb structure 10 passes through the honeycomb structures 60 and 70 on the downstream side, and the honeycomb structures 60 and 70 respectively perform predetermined functions, thereby purifying the exhaust gas.

[0128] Fig.11 (a) to (c) are related to Fig. 9 Schematic diagrams of exhaust gas purification systems 51, 52, and 53 in embodiments of the present invention are shown in FIG. 5, which have different configurations of exhaust gas purification system 50. The combination of catalyst carriers is the same in the three embodiments, but the induction heating portion is different depending on the purpose of heating. Fig.11 In (a) to (c), "DOC" means oxidation catalyst, "SCR" means selective reduction catalyst, "CSF" means oxidation catalyst, "Urea" means urea, "HC" means hydrocarbon, "ASC" means ammonia slip catalyst, "cc-" means directly under the engine, and "UF" means under the floor. Fig.11 The embodiments shown in (a) to (c) are also examples of implementing the present invention, and the exhaust gas purification system of the present invention is not limited to these embodiments.

[0129] Fig.11 In the exhaust gas purification system 51 shown in (a), in order to heat the oxidation catalyst (cc-DOC) directly below the engine at the most upstream of the gas flow, a conductor is provided on the upstream side of the gas flow of the honeycomb structure that carries the catalyst, and it is set as the honeycomb structure 10 involved in the embodiment of the present invention. According to such a configuration, by heating the oxidation catalyst (cc-DOC) at the most upstream, the purification performance of the system can be improved, and therefore, in particular, the problem of reduced purification performance of the system as a whole due to insufficient catalyst activity during low-temperature startup can be solved.

[0130] Fig.11In the exhaust gas purification system 52 shown in (b), in order to heat the oxidation catalyst (UF-DOC) under the floor, a conductor is set on the upstream side of the gas flow of the honeycomb structure that carries the catalyst, and it is set as the honeycomb structure 10 involved in the embodiment of the present invention. The hydrocarbon (HC) sprayed from the nozzle on the upstream side under the floor is oxidized by the oxidation catalyst (UF-DOC), and the heat generated by oxidation contributes to the increase in the exhaust gas temperature. As described above, by heating the UF-DOC by induction heating, the rise in the exhaust gas temperature can be promoted. In addition, for the honeycomb structure of the oxidation catalyst (UF-CSF) in the rear stage, a conductor is also set on the downstream side of the gas flow, and it is set as the honeycomb structure 10 involved in the embodiment of the present invention, thereby not only heating the honeycomb structure itself, but also heating the urea sprayed from the nozzle downstream thereof. According to this, the decomposition of urea into ammonia can be promoted, so that the SCR catalyst downstream thereof can function more effectively.

[0131] Fig.11 In the exhaust gas purification system 53 shown in (c), a conductor is provided on the upstream side of the gas flow of the honeycomb structure of the most downstream ammonia slip catalyst (ASC), which is the honeycomb structure 10 involved in the embodiment of the present invention. The purpose of the ammonia slip catalyst is to oxidize ammonia so as to suppress the emission of ammonia, a harmful substance, as an exhaust gas component into the external atmosphere. However, when the engine is started just after stopping, the activity of the catalyst is insufficient. In such a case, the purification performance can be improved by compensating it with induction heating.

[0132] Example

[0133] Hereinafter, examples are described for better understanding of the present invention and its advantages; however, the present invention is not limited to the examples.

[0134] <Example 1>

[0135] 30 g of magnetic powder with a composition of Fe-49 mass % Co-2 mass % V and an average particle size of 8 μm and glass frit with an average particle size of 2 μm were mixed at a mass ratio of 2:1, and a foaming resin for adjusting the porosity, carboxymethyl cellulose and water were further mixed therein to prepare a slurry. The obtained slurry was filled only on one side end face of a cylindrical cordierite honeycomb structure with a diameter of 82 mm, a length of 85 mm, a partition wall thickness of 0.1 mm, and a partition wall distance of about 1 mm, to a depth of 10 mm. Figure 2 The composite material was then sintered at 1000°C to form a composite material. In this case, the composite material was formed in an area corresponding to 12% of the total length of the honeycomb structure from one end face. The porosity of the composite material obtained was 58% after grinding, SEM, and image analysis.

[0136] Next, the honeycomb structure provided with the composite material was placed in a quartz glass tube with an inner diameter of 90 mm, and hot air heated to 200° C. was blown at a speed of 0.5 Nm / s. 3 / min flows into the quartz glass tube. Next, an induction heating coil with a diameter of 100mm is wound around the outer side of the end portion on the upstream side of the gas flow in a manner that can only heat the composite material arranged at a depth of 10mm from the end face on the upstream side of the gas flow of the honeycomb structure, and a heating test of the honeycomb structure is carried out using an induction heating device. The temperature of the end face on the upstream side of the gas flow of the honeycomb structure is measured using an infrared thermometer. The input power is set to 3-6kW, and the induction heating frequency is set to 450kHz, and the temperature rise performance of the honeycomb structure is measured. As the test result, Fig.10 A graph showing the relationship between time (seconds) and temperature (° C.) of Example 1 is shown in FIG.

[0137] <Comparative Example 1>

[0138] The composite material was provided by filling the slurry of Example 1 in cells over the entire length of a honeycomb structure having the same size as that of Example 1 and then sintering at 1000° C. In this case, the composite material forming region corresponded to an area of ​​100% of the entire length of the honeycomb structure from one end face.

[0139] Next, the honeycomb structure filled with the composite material was set in the same test device as above. However, the induction heating coil with a diameter of 100 mm was wound in such a way that the entire carrier containing the composite material could be heated as much as possible. Next, the heating performance was measured under the same conditions as in Example 1. As the test results, Fig.10 A graph showing the relationship between time (seconds) and temperature (° C.) in Comparative Example 1 is shown in FIG.

[0140] In Example 1 and Comparative Example 1, the weight of the magnetic body used for the composite material and the honeycomb structure as the heated body are the same, and the input power for induction heating is also substantially the same. Fig.10 As shown, it is understood that Example 1 is heated earlier and can effectively raise the temperature of the gas passing through the portion where the composite material including the magnetic body exists in the honeycomb structure.

[0141] Explanation of symbols

[0142] 10, 20, 30, 60, 70 honeycomb structure

[0143] 11 Outer wall

[0144] 12 Next Door

[0145] 13, 14 Composite materials

[0146] 15 compartments

[0147] 16 Conductors

[0148] 17 Cells

[0149] 18 Bonding material layer

[0150] 40 Exhaust Gas Purification Catalytic Converter

[0151] 43 Nozzle

[0152] 44 Metal pipe

[0153] 45 Mixer

[0154] 46 Inorganic mat material

[0155] 47 Coil wiring

[0156] 48 Electromagnetic shielding part

[0157] 50, 51, 52, 53 Exhaust gas purification system

Claims

1. A honeycomb structure for induction heating, which is a columnar honeycomb structure formed by bonding a plurality of columnar honeycomb units via a bonding material layer, The honeycomb structure for induction heating is characterized in that: The columnar honeycomb unit has an outer peripheral wall and a partition wall, the partition wall is arranged inside the outer peripheral wall and partitions a plurality of cells, and the plurality of cells penetrate from one end face to the other end face to form a flow path, A conductor is provided in the bonding material layer in a region of the honeycomb structure that is less than 50% of the total length from the end surface on the upstream side in the gas flow direction, The conductor is a conductor that generates heat due to a change in the magnetic field, The conductor is a porous body, The conductor is provided in a ring shape surrounding the plurality of honeycomb units.

2. The honeycomb structure for induction heating according to claim 1, characterized in that: The conductor is a magnetic body.

3. The honeycomb structure for induction heating according to claim 1, characterized in that: The partition walls and the outer peripheral wall are made of at least one ceramic selected from the group consisting of cordierite, silicon carbide, aluminum titanate, silicon nitride, mullite, and alumina.

4. The honeycomb structure for induction heating according to claim 1, characterized in that: The honeycomb structure has a diameter of 150 mm or more, or a volume of 3 L or more.

5. An exhaust gas purification catalyst, characterized in that: have: The honeycomb structure according to any one of claims 1 to 4; and a catalyst supported in the cells of the honeycomb structure, The catalyst is at least one selected from the group consisting of an oxidation catalyst, a three-way catalyst, a NOx storage reduction catalyst, a NOx selective reduction catalyst, a hydrocarbon adsorption catalyst, a hydrocarbon oxidation catalyst, a carbon monoxide oxidation catalyst, and an ammonia slip catalyst.

6. An exhaust gas purification system, characterized in that: have: The honeycomb structure A according to any one of claims 1 to 4, wherein the honeycomb structure A is arranged on the upstream side in the gas flow direction; and At least one honeycomb structure B is disposed on the downstream side of the honeycomb structure.

7. The exhaust gas purification system according to claim 6, characterized in that: The honeycomb structure A carries a diesel oxidation catalyst, and the honeycomb structure B includes a diesel particulate filter.

8. The exhaust gas purification system according to claim 6 or 7, characterized in that: The honeycomb structure B also includes: at least one selected from the group consisting of a honeycomb structure carrying a selective reduction catalyst, a honeycomb structure carrying a NOx storage catalyst, a honeycomb structure carrying an ammonia slip catalyst, a honeycomb structure carrying a three-way catalyst and a honeycomb structure carrying a hydrocarbon adsorption catalyst.

Citation Information

Patent Citations

  • Exhaust emission control device for internal combustion engine

    JP2019173600A

  • Catalyst carrier and method for producing same, and exhaust gas purification device

    JP2019188272A

  • Induction heating apparatus and methods

    US20180185789A1

  • Honeycomb structural body, exhaust gas purification device, exhaust system, and method for producing honeycomb structural body

    WO2020031434A1